1999
DOI: 10.1152/ajprenal.1999.277.4.f552
|View full text |Cite
|
Sign up to set email alerts
|

Nucleotides regulate NaCl transport in mIMCD-K2 cells via P2X and P2Y purinergic receptors

Abstract: Extracellular nucleotides regulate NaCl transport in some epithelia. However, the effects of nucleotide agonists on NaCl transport in the renal inner medullary collecting duct (IMCD) are not known. The objective of this study was to determine whether ATP and related nucleotides regulate NaCl transport across mouse IMCD cell line (mIMCD-K2) epithelial monolayers and, if so, via what purinergic receptor subtypes. ATP and UTP inhibited Na(+) absorption [measured via Na(+) short-circuit current (I(Na)(sc))] and st… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

12
95
2

Year Published

2001
2001
2013
2013

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 72 publications
(109 citation statements)
references
References 33 publications
12
95
2
Order By: Relevance
“…However, in contrast to the data from cultured rabbit collecting duct cells, the effects of ATP were not dependent on PKC activation [370]. In a different model, mIMCD-K2 mouse collecting duct cells, apical (but not basolateral) nucleotides inhibited sodium reabsorption, an effect, which based on mRNA expression and pharmacological profiling, was attributed to activation of P2Y 1 , P2Y 2 , P2X3 and P2X4 receptors [238].…”
Section: Sodium Transportcontrasting
confidence: 70%
“…However, in contrast to the data from cultured rabbit collecting duct cells, the effects of ATP were not dependent on PKC activation [370]. In a different model, mIMCD-K2 mouse collecting duct cells, apical (but not basolateral) nucleotides inhibited sodium reabsorption, an effect, which based on mRNA expression and pharmacological profiling, was attributed to activation of P2Y 1 , P2Y 2 , P2X3 and P2X4 receptors [238].…”
Section: Sodium Transportcontrasting
confidence: 70%
“…Schwiebert et al also documented the appearance of P2X 7 to a significant degree at the mRNA level in primary cultures of human polycystic kidney disease (PKD) cells versus non-PKD human renal epithelial cell primary cultures as controls [101]. In a collaborative study with McCoy and Stanton, they showed expression of P2Y 1 and P2Y 2 as well as P2X 3 and P2X 4 in mIMCD-K2 cells [94]. In studies in mouse DCT cells by Quamme and coworkers and by Wingo and coworkers in mIMCD-3 cells, expression and function of both P2Y and P2X purinoceptors was concluded [92,93].…”
Section: Nucleotide and Nucleoside Receptor Expression Along The Nephronmentioning
confidence: 96%
“…P2X 6 is likely also expressed along most nephron segments, based on the work of Turner et al from the Unwin laboratory [86]. In collecting duct-cell models, the expression pattern shifted to P2X 3 and P2X 4 as the most abundantly expressed members [94,101]. Schwiebert et al also documented the appearance of P2X 7 to a significant degree at the mRNA level in primary cultures of human polycystic kidney disease (PKD) cells versus non-PKD human renal epithelial cell primary cultures as controls [101].…”
Section: Nucleotide and Nucleoside Receptor Expression Along The Nephronmentioning
confidence: 99%
“…How such enhancements of P2X 4 -like receptor function might lead to a potentiation of renal ENaC activity is still to be resolved, but a hint comes from a series of interconnected findings. First, McCoy et al reported that ATP responses in mIMCD-K2 cells were biphasic and comprised an initial reduction in sodium transport, followed by a small secondary rise [37]. Second, similar biphasic responses to serosally applied ATP were observed in frog skin epithelium, where the initial reduction in sodium transport occurred at the same time as a transient elevation in intracellular calcium, but the secondary rise in sodium transport was associated with the apical insertion of new sodium channels [43].…”
Section: Enac Modulation By P2rs In the Kidneymentioning
confidence: 91%
“…All apically expressed P2Rs inhibit ENaC, although the ability of P2Y receptors to inhibit ENaC is less than that in a (from 49-56% to 16%). The potentiating effect of apical P2X 4/6 receptors (when luminal Na + is low) has not been investigated over a 30-min period, but a potentiating effect of basolaterally expressed P2X 4 -like receptors has been reported in the immortalised K2-cell line from mouse inner medullary CD (mIMCD) [37]. Here, ATP or UTP (100 µM) caused only a modest reduction (~15%).…”
Section: Enac Modulation By P2rs In the Kidneymentioning
confidence: 97%